1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<696::aid-immu696>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A T cell activation antigen, Ly6C, induced on CD4+ Th1 cells mediates an inhibitory signal for secretion of IL-2 and proliferation in peripheral immune responses

Abstract: A T cell activation antigen, Ly6C, is considered to be involved in the autoimmunity of some autoimmune-prone mice; however, the function of Ly6C remains largely unknown. We prepared a rat anti-mouse Ly6C monoclonal antibody (mAb) (S14) that inhibits the proliferation of peripheral T cells stimulated with anti-CD3 mAb in vitro. S14 mAb, the specificity of which is confirmed by a cDNA transfectant, recognizes Ly6C antigen preferentially expressed on a part of CD8+ T cells in peripheral lymphoid organs. The immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…Ly6c is 21.1 cM from D15mit229 , and was poorly expressed in NOD thymocytes under all conditions (2.3-fold decrease; Figure 8). This reduced expression has been previously observed to be due to a Ly6c promoter polymorphism in NOD mice, and is thus a known cis effect [65]. Functionally, Ly6c inhibits the signal for secretion of interleukin (IL)2 and proliferation in peripheral CD4 + cells [65], and cross-linking of Ly6c causes clustering of Leukocyte function associated molecule 1 (LFA-1, CD11a/CD18) on the surface of CD8 T cells [66].…”
Section: Resultsmentioning
confidence: 99%
“…Ly6c is 21.1 cM from D15mit229 , and was poorly expressed in NOD thymocytes under all conditions (2.3-fold decrease; Figure 8). This reduced expression has been previously observed to be due to a Ly6c promoter polymorphism in NOD mice, and is thus a known cis effect [65]. Functionally, Ly6c inhibits the signal for secretion of interleukin (IL)2 and proliferation in peripheral CD4 + cells [65], and cross-linking of Ly6c causes clustering of Leukocyte function associated molecule 1 (LFA-1, CD11a/CD18) on the surface of CD8 T cells [66].…”
Section: Resultsmentioning
confidence: 99%
“…However, our studies reveal that Ly6C expression is associated with impaired proliferation and lack of differentiation into effector CTL following encounter with peptidepulsed iDC. Other studies have demonstrated that Ly6C expression may also be associated with reduced IL-2 production among CD4 ϩ T cells (28), which as a result, may affect the expression of CD25. Further studies have revealed that there is a deficiency in Ly6C expression among autoimmune susceptible mouse strains such as NOD and NZB (29), suggesting that low levels of Ly6C-expressing CD8 ϩ T cells may also be linked to failure of selftolerance induction.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the level of expression of Ly6C, as there is some evidence that expression of Ly6C may be associated with T cell anergy. Furthermore, a deficiency in Ly6C expression has been linked to autoimmunity (28,29). MACS-purified naive Thy1.1 ϩ CL4 CD8 ϩ T cells were labeled with CFSE and cocultured in the presence of iDC or mDC pulsed with K d HA peptide.…”
Section: Previous Studies Have Demonstrated That Naive Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules are found on hematopoietic cells as well as on other cells [12][13][14][15][16], and are all encoded by genes located on chromosome 15 [13]. Ly6C has previously been shown to be expressed on a subset of CD8 + T cells [17] and on NK1.1 + cells [18] representing both CD3 + NKT cells and CD3 -NK cells. Furthermore, Ly6C is expressed on a subset of macrophages [19].…”
Section: Introductionmentioning
confidence: 99%